Assessment of arterial whole blood redox potential during cardiopulmonary bypass - Vincent Pey; Marion Stephan; Pierre Gros; Cédric Dray; Fanny Bounes; Bertrand Marcheix; Vincent Minville; Anne Galinier; François Labaste (PLoS ONE, 2025)
Introduction Imbalance in the redox equilibrium is common in any type of aggression. Cardiopulmonary bypass (CPB) initiation induces metabolic perturbations, and reliable biological monitoring tools for this condition are currently limited (e.g., lactate/pyruvate ratio). The measurement of arterial whole blood redox potential (Eredox) provides a systemic assessment of the redox state and may serve as a valuable marker for detecting metabolic perturbations during CPB. In this prospective exploratory study involving patients undergoing cardiac surgery, we investigated variations in Eredox and lactate/pyruvate ratio during CPB initiation. Methods Using a prospective exploratory study design, we assessed the changes in Eredox and relevant variables during the initiation of CPB in 16 cardiac surgery patients. Results Upon initiation of CPB we observed a significant decrease in arterial whole blood redox potential (101.90 mV + /- 11.52 vs. 41.80 mV + /- 10,26; p < 0.0001). Concomitantly, the lactate/pyruvate ratio significantly increased (12.81 + /- 0.90 vs 67.1 + /- 7.94; p < 0.0001) while the acetoacetate/β-hydroxybutyrate ratio significantly decreased (1.11 + /- 0.19 vs. 0.54 + /- 0.05 at 0 min; p = 0.0055). The circulatory failure indicated by changes in the lactate/pyruvate ratio and ketone bodies at the initiation of CPB correlated with a significant reduction in Eredox. Conclusion Arterial Eredox is a novel variable that holds promise in the detection and monitoring of metabolic aggression during CPB. Its assessment during CPB initiation could provide valuable insights into the patient’s circulatory status, as the Eredox appears to be more sensitive than lactate for monitoring circulatory insufficiency.